Effect of curcumin-loaded photoactivatable polymeric nanoparticle on peri-implantitis-related biofilm - Tonon, Caroline Coradi [UNESP]; Panariello, Beatriz; Chorilli, Marlus [UNESP]; Spolidorio, Denise Madalena Palomari [UNESP]; Duarte, Simone (Elsevier, 2022)
Curcumin has been used as a photosensitizer (PS) for antimicrobial photodynamic chemotherapy (PACT). However, its low solubility, instability, and poor bioavailability challenge its in vivo application. This study aimed to synthesize curcumin-loaded polymeric nanoparticles (curcumin-NP) and determine their antimicrobial and cytotoxic effects. Nanoparticles (NP) were synthesized using polycaprolactone (PCL) as a polymer by the nanoprecipitation method. Curcumin-NP was characterized by particle size, polydispersity index and zeta potential, scanning electron microscopy, and curcumin encapsulation efficiency (EE). Curcumin-NP was compared to free curcumin solubilized in 10% DMSO as photosensitizers for PACT in single and multispecies Porphyromonas gingivalis, Fusobacterium nucleatum, and Streptococcus oralis biofilms. Chlorhexidine 0.12% (CHX) and ultrapure water were used as positive and negative controls. The cytotoxic effect of curcumin-NP was evaluated on human periodontal ligament fibroblast cells (HPLF). Data were analyzed by ANOVA (α=0.05). Curcumin-NP exhibited homogeneity and stability in solution, small particle size, and 67.5% EE of curcumin. Curcumin-NP presented reduced antibiofilm activity at 500 µg/ml, although in planktonic cultures it showed inhibitory and bactericidal effect. Curcumin-NP and curcumin with and without photoactivation were not cytotoxic to HPLF cells. Curcumin-NP has antimicrobial and antibiofilm properties, with better effects when associated with blue light, being a promising therapy for preventing and treating peri-implant diseases.
Keywords: Curcumin; Fusobacterium nucleatum; Nanoparticle; Photo-inactivation; Photodynamic Therapy; Porphyromonas gingivalis; Streptococcus oralis